2018
DOI: 10.1021/acs.iecr.8b01720
|View full text |Cite
|
Sign up to set email alerts
|

Facile Approach To Design Thermally Safe Operating Conditions for Isoperibolic Homogeneous Semibatch Reactors Involving Exothermic Reactions

Abstract: To prevent thermal runaway incidents in semibatch reactors (SBRs), designing thermally safe operating conditions should be considered first. Regretfully, determination of the reaction kinetics for organic reactions is a timeconsuming and money-consuming process, especially in the fine chemical and pharmaceutical industries. Therefore, it is desirable to develop kinetic-parameter-free methods that can design the right operating conditions. Along this line, a new facile approach to design thermally safe operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…A comparison of the elaborated safety diagram and temperature diagram to other criteria is shown in Table 1 . The criteria of divergence and Morbidelli–Varma were compared with the safety boundary diagram by Westerterp et al 13 The result showed that the divergence criterion is too conservative, indicating a higher T cool as a critical temperature. The results of the Morbidelli–Varma criterion and the safety diagram were well-matched.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the elaborated safety diagram and temperature diagram to other criteria is shown in Table 1 . The criteria of divergence and Morbidelli–Varma were compared with the safety boundary diagram by Westerterp et al 13 The result showed that the divergence criterion is too conservative, indicating a higher T cool as a critical temperature. The results of the Morbidelli–Varma criterion and the safety diagram were well-matched.…”
Section: Resultsmentioning
confidence: 99%
“…This is because it is difficult to decide whether the reactants are completely consumed only by reaction calorimetry tests. In our previous work, 30 a solution to this problem has been proposed. In the following, we briefly introduce this solution.…”
Section: Approach To Design Qfs Operations Formentioning
confidence: 99%
“…According to our previous work, 12 when the dosing period (t D ) is 3800 s and the T j = 90 °C in the laboratory reactor, the corresponding isoperibolic operations must be perofrmed in the QFS region. However, the value of MTSR is experimentally determined to be higher than 117.9 °C.…”
Section: Case Studymentioning
confidence: 99%
“…Since the goal of this work is to develop a kinetics-free approach to scale up isoperibolic SBRs, the method to determine QFS operation conditions in the laboratory reactor should also be kinetics-free. In our previous work, , a kinetics-free approach to design QFS operations in SBRs has been developed on the basis of the fact that, as long as the MTSR values increase with the reaction temperature under isothermal operation, the corresponding isoperibolic homogeneous SBRs must be in the QFS situation, regardless of the values of Wt .…”
Section: Approach For Safe and Productive Scaleupmentioning
confidence: 99%
See 1 more Smart Citation